2017
DOI: 10.20960/nh.212
|View full text |Cite
|
Sign up to set email alerts
|

Association of 4-hydroxynonenal with classical adipokines and insulin resistance in a Chinese non-diabetic obese population

Abstract: Background: The prevalence of obesity is increasing worldwide. Oxidative stress plays an etiological role in a variety of obesity-related metabolic disorders. 4-hydroxynonenal (4-HNE) is the most abundant and reactive aldehydic product derived from the peroxidation of n-6 polyunsaturated fatty acids with diverse biological effects that are not well detailed. Obesity is associated with decreased plasma adiponectin concentrations and increased production of lipid peroxidation products, including 4-HNE, in adipos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…(995) 4-HNE levels are also elevated in the non-diabetic obese population. (996) This may be partly caused by a decrease in GST-α4(997) and concomitant decrease in HNE metabolism. (998) HNE upregulation has several effects associated with diabetes including promoting adiposeness and insulin resistance.…”
Section: Res/ros Signaling In Disease and Therapeutic Interventionsmentioning
confidence: 99%
“…(995) 4-HNE levels are also elevated in the non-diabetic obese population. (996) This may be partly caused by a decrease in GST-α4(997) and concomitant decrease in HNE metabolism. (998) HNE upregulation has several effects associated with diabetes including promoting adiposeness and insulin resistance.…”
Section: Res/ros Signaling In Disease and Therapeutic Interventionsmentioning
confidence: 99%
“…Our findings are consistent with numerous studies regarding the interrelationships between adipose tissue metabolism, inflammation, and cellular oxidative stress. Hyperleptinemia has been reported to be associated with increased production of lipid peroxidation products: HNE and MDA, as well as, increased protein oxidation, expressed as carbonyl content [40][41][42].…”
Section: Variablementioning
confidence: 99%
“…Studies have demonstrated that AGEs/ALEs can affect the cellular function of adipocytes, particularly the synthesis and secretion of adipokines [ 38 , 39 ]. In non-diabetic obese individuals, 4-hydroxynonenal, the main reactive carbonyl species target of carnosine, was positively correlated with leptin [ 40 ]. AGE concentrations were positively and independently associated with leptin concentrations in patients with type 2 diabetes [ 41 ].…”
Section: Discussionmentioning
confidence: 99%